Shifting Voting Patterns in Ghana’s Fourth Republic - Essuman-Johnson (Faculty of Social Studies, UG, 2007)
Ghana’s political tradition from the days of the nationalist struggle for independence has been a dual tradition of Nkrumah and Danquah/Busia. This tradition influenced voting behaviour in the first, second and third republics when the electorates decided mainly between candidates of the two traditions. This paper argues that from the beginning of the fourth republic there has been a shift in voter support from the Nkrumah/CPP – Danquah/Busia tradition to a Rawlings/NDC – Danquah/Busia tradition. It is argued that the shift has been caused by the ten-year rule of Rawlings – PNDC regime which facilitated the rise of a new tradition – the Rawlings/NDC tradition to emerge. The paper further notes that this new political tradition has supplanted the Nkrumah/CPP tradition in the four elections that have been conducted under the fourth republican constitution; but since 1996 there has been a gradual shift in voter preference from the Rawlings/NDC tradition to the Danquah/Busia tradition currently represented by the NPP